PENGARUH TEBAL DINDING TERHADAP STABILITAS DINDING PENAHAN TANAH PADA RENCANA RETAINING WALL JALAN MUALLAF KECAMATAN TENGGARONG - Ronaldi, Adji Raymond (KURVA S JURNAL MAHASISWA, 2014)
Tenggarong District which is the capital of Kutai regency of course requiregood road infrastructure, as this is one of the veins, especially in the area of theCapital District, both as infrastructure and as a mode of transportation andsupporting the economic development of society. In general, landslides arefrequent natural disaster when the rainy season arrives. Landslides caused bythe movement of the material making up a slope or the road consisting of soil,rock, or a mixture of the two materials, which then undergoes mass transfer orhave movement follows the shape of the slope or the road.In some cases retaining wall construction also experienced structuralfailure or not capable of withstanding the load acting due to rolling and sliding.Failure of retaining wall construction on the course should be studied fromvarious aspects, including the dimensions used on the construction of retainingwall. As a major part of the load bearing wall thickness of the soil pressure onretaining wall kosntruksi needs to be studied in the design so as to get a robustdesign and economical.In this study, given the restrictions that are more focused on the type ofconstruction of a retaining wall that is used is the type counterfort, loads aretaken into account in the design consists of dead load, additional dead load,traffic load, the load pressure of the soil and earthquake loads, variations inthickness below the retaining wall used are two variations of thickness 0,450meters and 0,250 meters and the quality of concrete used is K.325, or 325kg/cm2. From the calculation of the construction of retaining walls that arereviewed against the wall thickness is found that the largest axial force thatworks on both the thickness variation is 1208,1509 KN greatest shear forcesworking on x-axis direction retaining wall of 1115,7013 KN. From thecalculation shows that the thick wall retaining wall will affect the ability of thewall withstand moments around, so that the thicker wall retaining the abilitywalls hold bolsters will be even greater, and vice versa thinner walls, hence theability of the wall withstand bolsters will be smaller. While the influence of thewall thickness due to the shear force is not significant.